PERISTILAHAN TRADISI RAYE KUBBOR PADA MASYARAKAT DESA LUMBANG KECAMATAN SAMBAS KABUPATEN SAMBAS - Auliya', Nuria Zahratul; Patriantoro, Patriantoro; Heryana, Nanang (Universitas Tanjungpura, 2024)
This research aims to classified data obtained from the field, doing a data inventory in the form of terminology, lexical meaning, grammatical meaning, and cultural meaning, as a plan of implementation in Indonesian Language learning based on traditional terminology